2003
DOI: 10.1523/jneurosci.23-15-06392.2003
|View full text |Cite
|
Sign up to set email alerts
|

Purkinje Cell Synapses Target Physiologically Unique Brainstem Neurons

Abstract: The cerebellum controls motor learning via Purkinje cell synapses onto discrete populations of neurons in the deep cerebellar nuclei and brainstem vestibular nuclei. In the circuitry that subserves the vestibulo-ocular reflex, the postsynaptic targets of Purkinje cells, termed flocculus target neurons (FTNs), are thought to be a critical site of learning. Little is known, however, about the intrinsic cellular properties of FTNs, which are sparsely distributed in the medial vestibular nucleus. To identify these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 35 publications
7
75
0
Order By: Relevance
“…Prior work has further shown that neurons that receive inputs from the flocculus are type B neurons (Babalian and Vidal 2000;Sekirnjak et al 2003). Thus at least a subset of type B cells that have been described in in vitro studies are likely to correspond to the floccular target/eye-head neurons that have previously been described in in vivo studies and have been shown to play an important role in visually induced VOR motor learning in primates (Blazquez et al 2006;Lisberger et al 1994).…”
Section: Bridging the Gap: The Relation Between In Vivo And In Vitro mentioning
confidence: 83%
“…Prior work has further shown that neurons that receive inputs from the flocculus are type B neurons (Babalian and Vidal 2000;Sekirnjak et al 2003). Thus at least a subset of type B cells that have been described in in vitro studies are likely to correspond to the floccular target/eye-head neurons that have previously been described in in vivo studies and have been shown to play an important role in visually induced VOR motor learning in primates (Blazquez et al 2006;Lisberger et al 1994).…”
Section: Bridging the Gap: The Relation Between In Vivo And In Vitro mentioning
confidence: 83%
“…Cerebellar slices were prepared from either C57BL/6 or L7-GFP (C57BL/6 background) (Sekirnjak et al, 2003) mice on postnatal day 15 (P15) to P29 (mean of P21). When noted, experiments were done on Wistar rats, aged P36 -P39.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of a cerebellar inhibition in some phasic 2°VNs makes these neurons equivalent to mammalian floccular target neurons (FTN) in the MVN (De Zeeuw et al, 1994;Lisberger, 1998). In rodents, these neurons were shown to form a specific subpopulation of type B MVN neurons (Babalian and Vidal, 2000;Sekirnjak et al, 2003). Thus, a differentially organized Purkinje cell-mediated inhibition in equivalent subpopulations of vestibular neurons seems to be another conserved feature of vertebrate vestibular signal processing.…”
Section: Inhibitory Control Of Vestibular Responsesmentioning
confidence: 99%